Pentingnya Human Relations dalam Kegiatan Kehumasan - Rosyidi, Imron (Jurnal Ilmu Dakwah, 2009)
The core point of human relations has been hospility, respect, emphaty and honesty. Human relations may be implemented as a wide range of human interactions including business, government, school and other social institutions. Human relation has been a way by which a manager encourage staffs to work together with such productive maneuvers to produce a symbiotic complementary. This approach is necessary for a manager in an attempt to orient staffs in achieving corporate goals. This will certeaintly lead to overall success of both individuals and corporate.